Pipelines 2020 Planning and Design - Pulido, J. Felipe; Poppe, Mark (American Society of Civil Engineers, 2020)
Selected papers from Pipelines 2020, held in San Antonio, Texas, August 9-12, 2020. Sponsored by the Utility Engineering and Surveying Institute of ASCE.This collection contains 48 peer-reviewed papers on the planning and design of pipelines.Topics include: asset management; cathodic protection; rehabilitation design; large diameter design; seismic design; and design-build case studies.This valuable resource for practitioners and researchers covers the most current state-of-the-art engineering technologies for pipeline and utilities infrastructure and engineering surveying.
Keywords: Earthquake engineering.; elektronické knihy; electronic books